Assessment of Insulin Resistance in Subjects with Normal Glucose Tolerance, Hyperinsulinemia with Normal Blood Glucose Tolerance, Impaired Glucose Tolerance, and Newly Diagnosed Type 2 Diabetes (Prediabetes Insulin Resistance Research). (7th December 2015) - Yang, Guang; Li, Chunlin; Gong, Yanping; Fang, Fusheng; Tian, Hui; Li, Jian; Cheng, Xiaoling
Abstract : Aim. To evaluate the differences in insulin resistance (IR) among subjects with normal glucose tolerance (NGT), hyperinsulinemia with NGT (HINS), impaired glucose tolerance (IGT), and newly diagnosed type 2 diabetes mellitus (T2DM). Methods. 5 NGT, 25 HINS, 25 IGT, and 25 T2DM subjects participated in this research. The hyperinsulinemic-euglycemic clamp technique (HECT) was performed in all of them to evaluate IR levels. The relative factors influencing IR were evaluated. The simple insulin sensitivity indices were calculated, and the correlation between each index and the M value was analyzed. Results. TheM values of NGT, HINS, IGT, and T2DM groups were 11.88 ± 2.93 mg·kg −1 ·min −1, 6.23 ± 1.73 mg·kg −1 ·min −1, 6.37 ± 2.12 mg·kg −1 ·min −1, and 6.19 ± 1.89 mg·kg −1 ·min −1, respectively.M values in HINS, IGT, and T2DM groups were lower than those in the NGT group (P = 0.005 ); however, the differences among the HINS, IGT, and T2DM groups were not statistically significant (P = 0.835 ). The independent factors influencing theM value were waistline and fasting insulin level (FINS). The simple insulin sensitivity indices, especially Matsuda and Gutt index, were significantly associated with theM value (P < 0.01 ). Conclusion. IR existed in the HINS, IGT, and T2DM groups, and IR levels were consistent in the three groups. The independent factors influencing IR were waistline and FINS.